2011
DOI: 10.3109/09537104.2011.597528
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyper-reactivity of platelets resulting in enhanced monocyte recruitment in patients after ischaemic stroke

Abstract: Although the platelet activation profile after stroke is a well-known issue, the platelet reactivity assessed prospectively after ischaemic stroke still remains equivocal. The aim of this study was to evaluate the reactivity of platelets in response to stimulation with thrombin receptor-activating peptide (TRAP) at 1, 10 and 90 days after ischaemic stroke and to compare it with results obtained in control groups. We determined the increment in surface expression of CD62P, CD40L and monocyte- and granulocyte-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Ample evidence testifies the effectiveness of aspirin for reducing stroke recurrence [30]. With a few exceptions [6,23], previous work has revealed enhanced reactivity and increased platelet activity in acute stroke [19]. It, therefore, appears that the findings of this study are not consistent with earlier science or with up-to-date clinical practice.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Ample evidence testifies the effectiveness of aspirin for reducing stroke recurrence [30]. With a few exceptions [6,23], previous work has revealed enhanced reactivity and increased platelet activity in acute stroke [19]. It, therefore, appears that the findings of this study are not consistent with earlier science or with up-to-date clinical practice.…”
Section: Discussionmentioning
confidence: 58%
“…Conflicting data further exists with respect to circulating P-selectin. In acute stroke, concentrations of the protein appear to increase [6]. Still, other scientists have been unable to demonstrate soluble P-selectin alterations in stroke [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD154 is released into blood circulation as soluble CD154 (sCD154) [37] . When sCD154 binding to their cell surface receptor then exhibit proinflammatory and procoagulant properties, due that triggers the expression of interleukin (IL)-1, IL-6, IL-12, TNF-alpha, interferon-gamma [38] , tissue factor [39][40][41][42] , and binding to the glycoprotein IIb/IIIa platelet receptor [43,44] .There have been found a higher CD154 expression in platelet of ischemic stroke patients than in controls subjects [45,46] , higher circulating levels of sCD154 in ischemic stroke patients than in controls subjects [47][48][49][50][51][52][53][54] , and a higher CD154 expression in platelet of ischemic stroke patients with poor functional outcome compared with patients with better outcome [55,56] .In a study by our team were found higher serum levels of sCD154 in MMCAI patients than in healthy subjects [57] . In addition, we found an association between circulating levels of sCD154 and severity of stroke assessed by GCS (p = 0.04) for the first time.…”
mentioning
confidence: 99%